PERANAN SATUAN RESERSE KRIMINAL RESOR KOTA PEKANBARU DALAM PENYIDIKAN TINDAK PIDANA PERBUATAN CURANG YANG DILAKUKAN OLEH CALO CALON PEGAWAI NEGERI SIPIL DI KOTA PEKANBARU - Retno Andreas; Erdianto Effendi; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
There are many ways to get this job mainly illegally through brokers recruitment of civil servants. In this case relates to the role of the Criminal Investigation Unit Pekanbaru City resort in Deeds Cheating Crime Investigation Conducted by Calo candidate for Civil Servants. The purpose of this thesis, namely; first, the role of the Criminal Investigation Unit Pekanbaru City resort in the investigation of criminal acts committed by fraudulent brokers civil servant candidates, second, barriers experienced by the Criminal Investigation Unit Pekanbaru City resort in the investigation of criminal acts committed by fraudulent brokers prospective civil servant , third, the efforts made by Satreskrim resort town of Pekanbaru in overcoming the obstacles that arise in the investigation of criminal acts committed by fraudulent brokers civil service candidates. This type of research can be classified into types of sociological research. This study was performed in Pekanbaru City Police , while the overall population and the sample is related to the issues examined in this study, the data source used, primary data , secondary data and data tertiary data collection techniques in this study with questionnaires, interviews and literature study. From the research there are three basic problems that can be inferred. First, Role Satreskrim resort city of Pekanbaru in the investigation of criminal acts committed by fraudulent brokers civil servant candidates accomplished in accordance with the Code of Criminal Procedure. Second, barriers experienced by Satreskrim resort town of Pekanbaru in the investigation of criminal acts committed by fraudulent brokers civil service candidates, namely the lack of evidence of the complainant, witnesses were difficult to come by, no clear division of tasks between the units Satreskrim as well as the suspect who had escaped. Third, efforts made by Satreskrim resort town of Pekanbaru in overcoming the obstacles that arise, namely to disseminate the importance of awareness of the law, not give sufficient evidence, find suspects, increasing the number of investigators. Suggestions writer, first, the expected role Satreskrim Pekanbaru City resort in the investigation of criminal offenses fraudulent acts committed by brokers candidates Civil servants should be implemented with Effective in accordance with the duties and responsibilities, Second, barriers experienced by Satreskrim Pekanbaru City resort in the investigation of criminal acts The cheaters must be completed properly. Third, efforts made by Satreskrim resort town of Pekanbaru in overcoming the obstacles that arise in order to be implemented so that cases brokers candidate reception civil servants can be resolved. Keywords : Role - Investigator - Fraud - Calo - Civil Servant